Subcutaneous Abscess Secondary to Xanthogranulomatous Cholecystitis - Correia, Hugo (2014)
One of the known complications of gallstones consists in gallbladder perforation with cholecystocutaneous abscesses or external fistulas formation. Nowadays these types of complications are uncommon, having been more frequent. The authors report the case of an 86 year-old woman, bedridden and dependent, referred to our institution by presenting a tumefaction with inflammatory signs in the right upper quadrant. The radiological investigation revealed it to be a subcutaneous abscess associated with a perforated gallbladder, whose histological analysis revealed xanthogranulomatous cholecystitis.Keywords: Abscess; Cholecystitis; Granuloma; Xanthomatosis; Subcutaneous Tissue.